Nutritional Status and Associated Risk Factors of Syrian Children’s Residents in the Kingdom of Saudi Arabia - Khaled M. AlZoubi (MDPI AG, 2021)
This study aimed to evaluate the nutritional status and associated risk factors of Syrian children living in Saudi Arabia. In this study, 55 boys and 55 girls ranging in age from 6 to 12 years were selected. Socioeconomic data of families were collected using a structured questionnaire. The participants’ anthropometric measurements were calculated. The 24-h recall method was applied to calculate the daily food intake. Dietary nutrients’ average daily intake of both boys and girls was significantly (p ≤ 0.01) lower than that of the dietary reference intake (DRI) with few exceptions. The sedentary lifestyles of both boys and girls had a negative impact on their food choices, and as a result, a large number of them were underweight and suffered from malnutrition and stunting. Spearman correlation coefficients revealed that most of the children’s dependent variables were risk factors and strongly and negatively associated with their nutritional status proxies. The study concluded that both boys and girls had unbalanced nutritional status with high percentages of malnutrition and stunting because most dependent factors were adversely related to the independent ones.